2003
DOI: 10.1007/s00134-002-1555-4
|View full text |Cite
|
Sign up to set email alerts
|

End-expiratory lung impedance change enables bedside monitoring of end-expiratory lung volume change

Abstract: EIT is a simple bedside technique which enables monitor lung volume changes during ventilatory manoeuvres such as PEEP changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
171
0
12

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(191 citation statements)
references
References 26 publications
8
171
0
12
Order By: Relevance
“…[8][9][10][11] Corley et al 8 used electrical lung impedance tomography to assess changes in lung volume. 28,29 They showed that HFNC was associated with an increase in end-expiratory lung volume and confirmed the generation of positive oropharyngeal pressure reported in earlier studies. Moreover, they reported a significant correlation between end-expiratory lung impedance and airway pressure and demonstrated that at least part of the improvement in oxygenation in subjects with acute hypoxemic respiratory failure was due to alveolar recruitment.…”
Section: P Ao2 /F Io2supporting
confidence: 78%
See 2 more Smart Citations
“…[8][9][10][11] Corley et al 8 used electrical lung impedance tomography to assess changes in lung volume. 28,29 They showed that HFNC was associated with an increase in end-expiratory lung volume and confirmed the generation of positive oropharyngeal pressure reported in earlier studies. Moreover, they reported a significant correlation between end-expiratory lung impedance and airway pressure and demonstrated that at least part of the improvement in oxygenation in subjects with acute hypoxemic respiratory failure was due to alveolar recruitment.…”
Section: P Ao2 /F Io2supporting
confidence: 78%
“…The difference between HFNC and CPAP was not significant (23 [18 -25] breaths/min versus 21 [21][22][23][24][25][26][27][28][29][30][31][32] breaths/min, P ϭ .9) (Fig. 2).…”
Section: Effects On Oxygenation and Ventilationmentioning
confidence: 99%
See 1 more Smart Citation
“…A good correlation has been previously demonstrated between changes in lung impedance measured by EIT and changes in lung volume, 30,[33][34][35][36][37] suggesting that the application of high-flow therapy could increase functional residual capacity. This finding was already reported in a recent study, 19 where HFNC significantly increased global EELI in a population of post-cardiac surgery patients with respiratory dysfunction.…”
Section: Discussionmentioning
confidence: 69%
“…[27][28][29] Interestingly, good correlations have been found between changes in end-expiratory lung impedance (EELI) and changes in end-expiratory lung volume (EELV), 30,31 which is equivalent to functional residual capacity in nonintubated subjects. Another important feature of EIT is the possibility of assessing regional changes of impedance.…”
Section: Introductionmentioning
confidence: 99%